Challenges to dialysis treatment during the COVID-19 pandemic: a qualitative study of patients’ and experts’ perspectives - Oviedo Flores, Krystell; Stamm, Tanja; Alper, Seth L.; Ritschl, Valentin; Vychytil, Andreas (Frontiers in Psychology, 2023)
The global COVID-19 pandemic transformed healthcare services in ways that have impacted individual physical and psychological health. The substantial health challenges routinely faced by dialysis-dependent patients with advanced kidney disease have increased considerably during the ongoing COVID-19 pandemic but remain inadequately investigated. We therefore decided to analyze and compare the perspectives of dialysis patients on their own needs and challenges during the COVID-19 pandemic with those of their professional healthcare providers through interviews with both groups. Methods: Qualitative study of seven in-center hemodialysis patients, seven peritoneal dialysis patients, seven dialysis nurses, and seven physicians at the Medical University of Vienna between March 2020 and February 2021, involving content analysis of semistructured interviews supported by a natural language processing technique. Results: Among the main themes emerging from interviews with patients were: 1) concerns about being a 'high-risk patient'; 2) little fear of COVID-19 as a patient on hemodialysis; 3) questions about home dialysis as a better choice than in-center dialysis. Among the main themes brought up by physicians and nurses were: 1) anxiety, sadness, and loneliness of peritoneal dialysis patients; 2) negative impact of changes in clinical routine on patients' well-being; 3) telehealth as a new modality of care. Conclusions: Preventive measures against COVID-19 (e.g., use of facemasks, distancing, isolation), the introduction of telemedicine, and an increase in home dialysis have led to communication barriers and reduced face-to-face and direct physical contact between healthcare providers and patients. Physicians did not perceive the full extent of patients' psychological burdens. Selection/modification of dialysis modality should include analysis of the patient's support network and proactive discussion between dialysis patients and their healthcare providers about implications of the ongoing COVID-19 epidemic. Modification of clinical routine care to increase frequency of psychological evaluation should be considered in anticipation of future surges of COVID-19 or currently unforeseen pandemics.